Political opportunity structure under the administration of President Benigno S. Aquino III: A case study of a social movement of informal settler families in the Philippines - San Pedro-Raymundo, Alicia
The study investigates how and why a movement of informal settler families in the Philippines engaged actively with the administration of President Benigno S. Aquino III in 2010 to 2016. The social movement, Kilos Maralita, originated from the Left movement in the country and was born out of the struggle for the ouster of former President Gloria Macapagal-Arroyo from 2005-2009. It had historically shun participation in invited spaces because it always expected an elite state to work against the interest of the poor. The Aquino Administration, while it had liberal tendencies, was still dominated by political leaders from traditional elite political clans who are generally wary and hostile to the Left and other challengers.